Attack Hijacks Domain Names of Internet-Addressing Organization. (Computer (00189162), 2008)
The article reports that the NetDevilz Turkish computer hacking group claimed responsibility for hacking into the Internet Corporation for Assigned Names and Numbers (ICANN), the organization responsible for coordinating the assignment of IP (Internet Protocol) addresses and domain names. The hackers hijacked several of ICANN's domain names, then did phishing scams against several Web sites, the article states. Other topics include additional attacks by the same group against IANA (Internet Assigned Numbers Authority), a group connected to ICANN.